Building Awareness of the Dangers of Stunting Generation Through Health Communication for Indonesian Worker at Pulau Penang Malaysia - Suraya Mansur; Novi Erlita; Gammara Lenggo Geni (International Journal Of Community Service, 2024)
The implementation of Community Service is the result of collaboration between the Communication Studies Program at Mercu Buana University and Pertubuhan Masyarakat Indonesia (PERMAI) Pulau Pinang, Malaysia. The Theme of Community Service Activities is Building Awareness of the Dangers of Stunting Generation Through Health Communication. To achieve this goal, the lecture method is used, playing youtube videos of short duration, then questions and answers about Building Awareness of the Dangers of Stunting Generation Through Health Communication For TKW women worker in Pulau Pinang, Malaysia. This campaign activity is planned to be held in January, 28. 2024 in Pulau Pinang, Malaysia. This activity is expected to be attended by women worker who live in Malaysia. Target outputs of this community services activity is increased knowledge and skill, Mass Media Publication, journal article, HAKI and video Activity. Lastly, the satisfaction of the participants in the devotion activities can be said to be very good. This can be seen from the response which says that the material delivered is in accordance with what is needed by the participants, besides that he also follows the activity from beginning to end. In addition, in terms of participants, it was seen from their cooperative attitude and feedback that was relevant to what was delivered by the speaker.